Implementasi Filsafat Pendidikan Islam Dalam Mengembangkan Kurikulum Pendidikan Islam - Romli, Ahmad Bagus Syifaur; Fajar Shodiq, Mohammad; Defri Juliansyah, Achmad; Mawardi, Munif; Yusron Maulana El-Yunusi, Muhammad (LP2M Universitas Islam Ahmad Dahlan, 2023)
The philosophy of Islamic education has shaped the framework of thought and the way education views life. In the world of education, the school curriculum is an important component that must exist in every educational unit. Likewise with schools or madrasas, if you want a good education, the methodology used is literature search or literature study. This methodology involves searching and analyzing various relevant sources, such as books, journal articles, and other publications related to the topic of the views of the philosophy of Islamic education on the Islamic education curriculum. The national goals in Indonesia can be seen in the applicable national education system law. Developing learning experiences learning experiences need to be compiled to provide teachers with ideas about the details of learning activities that must be carried out. The curriculum is a set of plans and documents intended to guide educational institutions in achieving the desired educational goals. Islamic education curriculum development is an unfinished activity. It must be carried out continuously both in the aspects of planning, implementation and evaluation based on Islamic values